Completed plastome sequence of Sophora moorcroftiana, an endemic shrub to the Qinghai-Tibet Plateau, China - Huie Li; Lan Yang; Qian Li; Jiangrong Li (Mitochondrial DNA. Part B. Resources, 2019)
Sophora moorcroftiana, an endemic Fabaceae species occurred in the Qinghai-Tibet plateau, China, has important economic value in local. Its completed plastome sequence is 148,930 bp in size, and comprises a pair of inverted repeat (IR) regions of 23,787 bp each, a large single-copy region of 83,342 bp and a small single-copy region of 18,014 bp. The GC content of the plastome was 30.2%. A total of 124 genes were identified, comprising 80 protein-coding genes, 36 tRNA genes and eight rRNA genes. There are 94 unique genes, with 15 genes duplicated in the IR regions. Phylogenetic tree shows that plastome of S. moorcroftiana is most related to that of S. alopecuroides. This plastome would be helpful for the study of molecular mechanism of photosynthesis, sustainable conservation, genetic improvement of S. moorcroftiana.